Theories of inequality an overview and a strategy for synthesis - Milner, Murray Jr. (1987., 1987)
The long debate between functional and conflict theories of social inequality has not been resolved largely because the issues have been inadequately formulated. This paper largely abandons this dichotomy and presents explicit models of five approaches to explaining inequality. These are then synthesized into a common framework. It is shown that stratification literature as divergent as status attainment models, the Davis' Moore theory, power elite studies, Lenski's evolutionary theory, Habermas' analysis of distorted communications, and world-systems theory can be subsumed under the framework.
Photocopy.
Includes bibliographical references (pages 1058-1089).
Keywords: Equality; Social analysis; Sociology